Cholestasis and hepatic ischemia : bile acids therapy. cellular mechanisms with relevance to mitochondrial function - Rolo, Anabela Pinto (2003)
Tese de doutoramento em Biologia (Biologia Celular) apresentada à Fac. de Ciências e Tecnologia de Coimbra